2020
DOI: 10.3390/ijms21082685
|View full text |Cite
|
Sign up to set email alerts
|

Vascular Calcification—New Insights into Its Mechanism

Abstract: Vascular calcification (VC), which is categorized by intimal and medial calcification, depending on the site(s) involved within the vessel, is closely related to cardiovascular disease. Specifically, medial calcification is prevalent in certain medical situations, including chronic kidney disease and diabetes. The past few decades have seen extensive research into VC, revealing that the mechanism of VC is not merely a consequence of a high-phosphorous and -calcium milieu, but also occurs via delicate and well-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
279
0
7

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 281 publications
(288 citation statements)
references
References 303 publications
(373 reference statements)
2
279
0
7
Order By: Relevance
“…Additionally, complex mechanisms are common in both intimal calcification and medial calcification. The mechanism included failed anti-calcification processes due to loss of calcification inhibitors including osteoprotegerin, osteopontin, matrix Gla protein (MGP), fetuin-A and pyrophosphate [48,[70][71][72][73], induction of osteo/chondroblast-like cells producing extracellular vesicles [74], cell death resulting in release of apoptotic bodies or necrotic debris that cause nucleation of apatite [75], calcium/phosphate dysregulation causing deposits calcium phosphate hydroxyapatite [76], nucleation complexes formed during bone remodeling, and matrix degradation/modification [77].…”
Section: Molecular Mechanisms Of Arterial Calcificationmentioning
confidence: 99%
“…Additionally, complex mechanisms are common in both intimal calcification and medial calcification. The mechanism included failed anti-calcification processes due to loss of calcification inhibitors including osteoprotegerin, osteopontin, matrix Gla protein (MGP), fetuin-A and pyrophosphate [48,[70][71][72][73], induction of osteo/chondroblast-like cells producing extracellular vesicles [74], cell death resulting in release of apoptotic bodies or necrotic debris that cause nucleation of apatite [75], calcium/phosphate dysregulation causing deposits calcium phosphate hydroxyapatite [76], nucleation complexes formed during bone remodeling, and matrix degradation/modification [77].…”
Section: Molecular Mechanisms Of Arterial Calcificationmentioning
confidence: 99%
“…VC refers to mineral deposition in the vascular system, in the form of Ca-P complexes [ 116 ]. Although VC is part of the normal aging process, some diseases such as diabetes, hypertension, and CKD can accelerate this process [ 116 , 117 , 118 ]. Vascular and other soft-tissue calcifications are a major problem in end-stage CKD.…”
Section: Caloric Intake and Vcmentioning
confidence: 99%
“…In CKD patients, medial artery calcification is the most prevalent form of VC and is associated with increased stiffness of the artery wall [ 119 ]. VC is one of the major contributors to cardiovascular mortality in these patients [ 116 , 118 ].…”
Section: Caloric Intake and Vcmentioning
confidence: 99%
“…Accumulating studies have demonstrated that VC is highly regulated by biological processes involving the transformation from the VSMC’s phenotype into osteoblast-like cells. VC is characterized by decreased expression of contractile proteins including smooth muscle 22 alpha (SM22α) and alpha-smooth muscle actin (α-SMA) [ 2 ], and increased expression of bone-related proteins such as runt-related transcription factor 2 (Runx2) [ 3 ] and bone morphogenetic protein 2 (BMP-2) [ 4 ].…”
Section: Introductionmentioning
confidence: 99%